2010
DOI: 10.5424/sjar/201008s1-1232
|View full text |Cite
|
Sign up to set email alerts
|

Growth response of maize plants (Zea mays L.) to wheat and lentil pre-cropping and to indigenous mycorrhizae in field soil

Abstract: The presence of indigenous mycorrhizal fungi may have significant effects on the growth and on the root morphology of plants, under arid and semi arid soil conditions. Lentil and wheat are the traditional crops grown in Southeastern Turkey. In this study soil samples from the Harran plain were collected from the 0-15 cm surface layer under wheat or lentil crop residues and used in a pot experiment carried out under greenhouse conditions with four levels of P fertilization: 0, 20, 40 and 80 mg kg -1 soil as Ca(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The results show that mycorrhizae inoculation is also vital for optimum growth. The results also indicate that a higher mycorrhizal colonization due to AM fungal inoculation was positively correlated with crop yields, and P and Zn uptake, which is agreement with the findings of Lekberg and Koide [6], and Almaca and Ortas [40]. Since plant tissue P and Zn concentrations after inoculation with indigenous AMF spore suspensions were less than the critical level and after inoculation with exotic AMF strains it was over the critical level, it is important to use mycorrhizal fungi to increase the plant nutrient concentration to an optimum level.…”
Section: Mycorrhizae Species Soilssupporting
confidence: 90%
See 2 more Smart Citations
“…The results show that mycorrhizae inoculation is also vital for optimum growth. The results also indicate that a higher mycorrhizal colonization due to AM fungal inoculation was positively correlated with crop yields, and P and Zn uptake, which is agreement with the findings of Lekberg and Koide [6], and Almaca and Ortas [40]. Since plant tissue P and Zn concentrations after inoculation with indigenous AMF spore suspensions were less than the critical level and after inoculation with exotic AMF strains it was over the critical level, it is important to use mycorrhizal fungi to increase the plant nutrient concentration to an optimum level.…”
Section: Mycorrhizae Species Soilssupporting
confidence: 90%
“…In addition, mycorrhizal inoculation had a significant effect on root colonization. Ortas [8], and Almaca and Ortas [40] have previously shown that mycorrhizal inoculation, under sterilized and non-sterilized soil conditions, significantly enhanced maize root colonization.…”
Section: Mycorrhizae Species Soilsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some studies report that increases in P levels reduce the development of mycorrhizal symbiosis; However, the levels at which such a reduction occurs are variable (Almaca and Ortas, 2010) and are based on the identity of the HMA species and the plant genotype (Lacerda et al, 2011). In this case, the interactions between mycorrhizal inoculation and the addition of phosphate fertilizer showed different effects.…”
Section: Discussionmentioning
confidence: 98%
“…In a field experiment conducted in the Turkish Mediterranean region, Celik et al (2004) indicated that organic fertilizer or/and inoculation with AMF spores could improve soil physical and chemical properties. It was indicated that the indigenous AMF isolated from the Mediterranean region can significantly contribute to plant growth and P uptake in Turkey (Aka-Kacar et al 2010;Almaca and Ortas 2010;Ortas 2010). These works have focused on AMF infection rate, spore morphology and density.…”
Section: Introductionmentioning
confidence: 99%